Asesmen Mengukur Peningkatan Kemampuan Siswa Dalam Proses Produksi Meja Melalui Teknik Bending Triplek Di SLB Paedagogia Surabaya - Widyastuti, Maria; Prabani Setio, Stefanus; Budi Hermanto, Yustinus; Zalianty Berlian, Putri; Nia Budiarti, Monica (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Disabled people have obstacles in normal activities, they sometimes find it difficult to adapt to the environment and tend to be alone. Behind the obstacles you have, there are abilities that need to be trained to be able to do difficult work. By empowering disabled people with training methods, we are able to bring out the talents and abilities of disabled people in furniture production activities. This activity was carried out on six SLB Pedagogia - Surabaya students. Students experience obstacles in hearing and speaking. while one alumni has mild mental retardation. The seven students have been trained to produce tables and chairs using plywood bending techniques. After they have been trained since 2022, in October 2024 an assessment was carried out to determine the students' abilities in producing tables. Assessment is carried out through observations of students doing production work. The assessment is assessed in seven production stages: 1) Lamination Process; 2) Bending Process; 3) Component Formation Process; 4) Filler Process; 5) Assembly Process; 6) Sanding Sealer Process; 7) Melamine Gloss Process. These seven stages are carried out by students so that their abilities can be seen. The results of the assessment show better capabilities in quality and faster production processes. This shows that people with disabilities will be able and empowered if coaching and training continues to be carried out so that it provides benefits for themselves and others.